Peningkatan Literasi Keamanan Perangkat Dan Aplikasi Bagi Generasi Muda Melalui Webinar PKM Nasional Tahun 2026 - Muhamad Azwar; Ondi Asroni; Tb Ai Munandar; Helna Wardhana (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
The rapid advancement of digital technology has led to a sharp increase in various cyber threat. This situation particularly affects the younger generation, who are the most active internet users. This community service activity was carried out through a national webinar as part of the 2026 National Community Service Collaboration Program organized by the Research and Community Service Network . The special session was designed to strengthen participants’ knowledge and awareness regarding the protection of devices and digital applications. Total of 190 participants from various regions in Indonesia joined the event online via Zoom Meeting. The session was included pre-test and post-test assessments using a seven-statement Likert-scale questionnaire (1–5). Analysis of data from 100 participants who fully completed both the pre-test and post-test showed a significant improvement in the average score, rising from 3.13 in the pre-test to 4.51 in the post-test, representing an increase of 44.1%. The highest improvements were observed in the understanding of free security tools (66.3%) and safe mobile application practices (48.6%). This webinar has made a real contribution to enhancing digital literacy and cyber security awareness among the younger generation in Indonesia.